V. Sosyura in the space of necessity and freedom (poetic collection "Near old mine" 1958) - Михайлин, Ігор Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The research is based on the idea of Yu. Shevelev that in the Soviet literature it is necessary to distinguish between a zone of necessity and a space of freedom. Artistic works contain a multivalued interpretation, and they must be taken into account in the modern reading of literature from the point of view of the truth reflected in it. The book of V. Sosyura contains three poems written in the spirit of socialist realism. But in the chapter "Poems" the lyric diary of the poet is reflected: poems about the granddaughter, wife, mother, grandmother, love, nature, approaching old age. The poet seeks to feel himself the part of Ukrainian patriarchal family, bypassing the official theme.